Reducing the crystallinity of PCL chains by copolymerization with substituted δ/ε-lactones and its impact on the phase separation of PCL-based block copolymers. Issue 15 (31st March 2022) - Kayser, Franck; Fleury, Guillaume; Thongkham, Somprasong; Navarro, Christophe; Martin-Vaca, Blanca; Bourissou, Didier
Abstract : Different self-segregation behavior of ABA triblock copolymers with central PBD or PBD H blocks and semi-crystalline or amorphous PCL-like external blocks. Abstract : Various substituted δ/ε-lactones have been copolymerized with ε-caprolactone (ε-CL) with the aim to inhibit the crystallization of polycaprolactone (PCL). Among the studied co-monomers, the best results were obtained with the 4-phenyl-ε-caprolactone (4-Ph-ε-CL) co-monomer. Its copolymerization with ε-CL using methane sulfonic acid (MSA) as ring-opening polymerization (ROP) organo-catalyst afforded highly random P(ε-CL- co -4-Ph-ε-CL) copolymers (the corresponding reactivity ratios have been determined as 0.67 for ε-CL and 0.60 for 4-Ph-ε-CL). DSC analyses revealed that amorphous samples were obtained when 20% or more of 4-Ph-ε-CL was incorporated into the PCL chains. The 4-Ph substituent is most efficient at preventing PCL crystallization by impeding chain folding and alignment, while it only slightly impacts the polymerization rate. Using telechelic dihydroxyl-terminated (hydrogenated) polybutadiene macroinitiators, MSA-catalyzed ROP chain extension led to well-defined triblock copolymers, as supported by NMR and SEC analyses. A combination of SAXS, WAXS and DMA studies revealed the intricate segregation behavior of these triblock copolymers with respect to the semi-crystalline vs. amorphous character of the PCL-type blocks.